Task Variation and Mental Models Divergence Influencing the Transfer of Team Learning. (October 2018) - Toader, Andra F.; Kessler, Thomas
We investigate how teams develop and transfer general problem-solving skills across two ill-structured problems. We draw on cognitive flexibility theory in the instructional literature and propose that teams will achieve a higher performance on a novel task or transfer when they receive an external task intervention (i.e., task variation) and when the internal mechanisms (i.e., divergent mental models) are developed to make sense of the external intervention. To test these predictions, we designed a longitudinal experiment with 17 student teams that encountered task variation during their work on an initial task. Consistent with our predictions, we found that teams that experienced variations and whose mental models diverged during their work on an initial task achieved higher performance on a novel task than teams that experienced variation and whose mental models converged. Implications for the transfer of learning in teams on ill-structured problems are discussed.